Predicting Systemic Banking Crises Using Early Warning Models: The Case of Montenegro - Željka Asanović (Journal of Central Banking Theory and Practice, 2017)
Very high costs of systemic banking crises emphasize the importance of early warning models for these crises. In order to create an early warning model for systemic banking crises a combined approach is implemented. The first approach applied in this paper is signal approach, however, with some modifications as compared with its standard application in the literature. On the basis of individual indicators two composite indices are created. Unlike other papers in this field, the author has chosen a 24-month period before the beginning of the crisis as a signal horizon, while the signal horizon in the literature is usually considered to be a period of 12 months before and 12 months after the crisis onset. The second approach represents logit model whereas the independent variables are actually the indicators with the best performances obtained within the signal approach. In order to check the robustness of indicators, the Bayesian model averaging technique is used. The indicator that represents the credit growth rate, besides being a part of the composite index, is statistically significant in all estimated specifications of the logit model, including the technique of Bayesian model averaging. Additionally, trends in the international market have a significant influence on the domestic banking system and its stability, and hence also on the probability of occurrence of a systemic banking crisis.
Keywords: G01; C25; C11; 330; early warning models; systemic banking crises; Montenegrin banking system; signal approach; composite index; logit model; Bayesian model averaging; synthesis of signal and logit approach; credit expansion; economic cycle.